IMPLEMENTATION OF HOT BATH HYDROTHERAPY AND MOIST WOUND HEALING INNOVATIONS IN NURSING CARE FOR SKIN INTEGRITY DISORDERS IN TYPE 2 DM PATIENTS IN THE ORCHID ROOM OF SUNGAILIAT REGIONAL GENERAL HOSPITAL IN 2026 - Mega Artika; Shindi Hapsari (PT. Radja Intercontinental Publishing, 2026)
Background: Type 2 Diabetes Mellitus often causes diabetic ulcers that cause impaired skin integrity and increase the risk of infection, amputation, and decreased quality of life. The combination of Hot Bath Hydrotherapy and Moist Wound Healing is a nursing innovation that has the potential to support wound healing. Objective: To describe the application of Hot Bath Hydrotherapy and Moist Wound Healing innovations in nursing care for type 2 Diabetes Mellitus patients with impaired skin integrity in the Anggrek Ward, Bakti Timah Hospital, Sungailiat in 2026. Method: The study used a descriptive design with a descriptive case study approach. The study subjects were 10 type 2 Diabetes Mellitus patients with diabetic ulcers who met the inclusion criteria. Data were collected using a nursing assessment format, wound development observation sheet, Bates-Jensen Wound Assessment Tool or Pressure Ulcer Scale for Healing, documentation, interviews, observations, and physical examinations. Data analysis was carried out descriptively by comparing the patient's condition before and after the intervention. Results: All patients showed improvement in wound condition in the form of reduced exudate and necrotic tissue, increased granulation tissue, decreased pain, reduced signs of infection, and increased mobility after 3 x 24 hours of intervention. Conclusion: The combination of Hot Bath Hydrotherapy and Moist Wound Healing has the potential to be an evidence-based nursing intervention that supports the healing of diabetic ulcers and improves the quality of nursing care.